Mid-Holocene East Asian summer monsoon and vegetation changes recorded by a stalagmite from Huangjin Cave, northern China - Bin Zhao; Yongjin Wang; Liang Ning; Qingfeng Shao; R. Lawrence Edwards; Yijia Liang; Kan Zhao (Quaternary Science Reviews, 2026)

Precision nanoparticles for plant thermotolerance: From molecular mechanisms to scalable agriculture - Muhammad Azeem Ashraf; Muhammad Ateeq; Muhammad Amjad; Qingfeng Dong; Hao Ren; Asad Shehzaib; Wang Xue; Liang Chen; Yin-Gang Hu (Plant Science, 2026)

Heterogeneous responses of the East Asian summer monsoon and hydroclimate in southwest China to Bond events during the Late Holocene - Bin Zhao; Tianxiang Fu; Zhigang Zhang; Kan Zhao; Zhenqiu Zhang; Qingfeng Shao; Yijia Liang; Yongjin Wang (Global and Planetary Change, 2026)

Macrocycle-size-modulated Cl− microenvironments in cationic mesoporous polymers for rapid capture of volatile iodine - Zhangjie Huang; Jinkai Qiu; Liang Liu; Qimeng Sun; Xiaoyong Xia; Cheng Lian; Dongyun Chen; Hua Li; Qingfeng Xu; Jianmei Lu (Chemical Engineering Journal, 2026)

Low-lethal and intergenerational effects of broflanilide on the diamondback moth, Plutella xylostella (L.) - Kunkun Wang; Qiqi Zhao; Chenyao Yang; Chen Shen; Qichao Zhang; Renwen Zheng; Pei Liang; Qingfeng Tang (Pesticide Biochemistry and Physiology, 2026)

A star’s death by a thousand cuts: the runaway periodic eruptions of AT2023uqm - Yibo Wang; Tinggui Wang; Shifeng Huang; Jiazheng Zhu; Ning Jiang; Wenbin Lu; Rongfeng Shen; Shiyan Zhong; Dong Lai; Yi Yang; Xinwen Shu; Tianyu Xia; et al. (Science Bulletin, 2026)

SfIML-1 interacts with integrin β5 to mediate fungal conidial adhesion and immune activation in Spodoptera frugiperda - Fang-Fang Liu; Qi-Gui Gao; Yue Sun; Chao-Peng Liang; Hai-Yan Ren; Qingfeng Tang; Liang Wen; Bang-Xian Zhang; Xiang-Jun Rao (Pesticide Biochemistry and Physiology, 2026)

Ecosystem collapses in Southwest China revealed by stalagmite records during the Mid-to-Late Holocene - Shaohua Yang; Chuntong He; Shitao Chen; Qingfeng Shao; Ye Zhu; Lei Lu; Hongwei Yin; Yijia Liang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Decoding future land use dynamics through neighborhood sequences: A cellular automata-inspired large language model framework (LLM-CA) - Xun Liang; Renyuan Zhang; Xin Quan; Qingfeng Guan (Applied Geography, 2026)

Solar forcing of abrupt climate change during early MIS 2: Insights from a 7-year-resolution stalagmite δ18O record in the Asian monsoon region - Pengfei Niu; Fucai Duan; Yifei Wang; Jianshun Chen; Yijia Liang; Qingfeng Shao; Yongjin Wang; Yongqiu Wu (Global and Planetary Change, 2026)

Contrasting response of the Asian Summer monsoon to bipolar climates and implications for ice core chronology during Marine Isotope Stages 5c-a inferred from stalagmite record, Central China - Zhenjun Wang; Shitao Chen; Yongjin Wang; Yalan Zeng; Li Wu; Yijia Liang; Gongzhe Chen; Zhenqiu Zhang; Shaohua Yang; Chunsheng Hu; Peng Sun; Qingfeng Shao; et al. (Global and Planetary Change, 2026)

Study on the effects of ultraviolet inactivation in the process of gynogenetic development of grass carp eggs induced by mirror carp sperm - Wangchao He; Yu Sun; Kuo Chen; Junwen Liang; Binchao Liang; Xinyan Zhu; Qingfeng Liu; Yang Chen; Jialin Tang; Fuzhong Yang; Chun Zhang; Bo Chen; et al. (Aquaculture, 2026)

Flow pattern regime of ventilated cavity around an axisymmetric body under a varying incoming flow velocity: an experimental study - Zichao Shao; Liang Hao; Yue Wu; Taotao Liu; Qingfeng Yang; Dongning Fan; Biao Huang (Ocean Engineering, 2026)

Regular and mechanism of millennial scale weak monsoon events during the late MIS7 to early MIS6.5 period - Shaohua Yang; Shitao Chen; Yongjin Wang; Bin Zhao; Yijia Liang; Zhenjun Wang; Zhenqiu Zhang; Quan Wang; Qingfeng Shao; Lei Lu; Chuan-Chou Shen (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Early Holocene monsoon abrupt changes and hydrological response as recorded by a multi-proxy stalagmite from Yuquan Cave, Central China - Xiaomeng Cui; Junji Zhu; Kan Zhao; Jiangying Wu; Yijia Liang; Liang Ning; Qingfeng Shao; Yongjin Wang (Science China Earth Sciences, 2026)

Zinc oxide nano-priming fortifies Triticum aestivum L. against salt stress through physio-morphological, biochemical and transcriptomic responses - Muhammad Ateeq; Muhammad Azeem Ashraf; Qingfeng Dong; Hao Ren; Tauqeer Ahmad Yasir; Linzhou Huang; Liang Chen; Yin-Gang Hu (Plant and Soil, 2026)

Evolution of Asian summer monsoon and vegetation in southwestern China and their linkages with wildfire history during the Holocene - Bin Zhao; Yijia Liang; Yongjin Wang; Kan Zhao; Qingfeng Shao; Hai Cheng (Global and Planetary Change, 2026)

Multi-trait analysis to identify key factors influencing wheat lodging resistance and validation of an integrative lodging index - Hao Ren; Qingfeng Dong; Siting Li; Dezheng Liu; Xubin Zhang; Xue Wang; Liang Chen; Yin-Gang Hu (European Journal of Agronomy, 2026)

Keratan sulfate revisited: UPLC–MS/MS-based quantitative profiling reveals structural heterogeneity and deficiency in ocular pathologies - Xinping Wang; Han Zhou; Xi Liang; Yue Li; Shimei Shen; Yuxin Li; Qingfeng Niu; Bi Ning Zhang; Shuying Xu; Guangli Yu; Guoyun Li (Carbohydrate Polymers, 2026)

Discovering the causal mechanism of day-night extreme heat driven by 2D and 3D urban landscape changes: a case study of Wuhan, China - Yingqiang Zhong; Shaochun Li; Xinmeng Zhou; Xun Liang; Qingfeng Guan (Sustainable Cities and Society, 2026)

The tripartite 4.2 ka event in East Asia: Stalagmite evidence and its interregional implications - Zhenqiu Zhang; Weihong Zhang; Zhiyuan Shang; Jianshun Chen; Yijia Liang; Qingfeng Shao; Kan Zhao; Yongqiu Wu; Yongjin Wang (Global and Planetary Change, 2026)

Two-phase structure optimization of Al-doped Ag1.995Te0.5S0.5 for improved mechanical and thermoelectric properties - Min Zhu; Xiao-Lei Shi; Hao Wu; Meng Li; Wei-Di Liu; De-Zhuang Wang; Liang-Cao Yin; Wen-Yi Chen; Yan Huang; Zhi-Gang Chen; Qingfeng Liu (Chemical Engineering Journal, 2026)

Macrocyclic Schiff-base covalent organic polymers with synergistic multi-sites for high-temperature iodine/methyl iodide capture - Liang Liu; Zhonglin Ma; Jiaqing Huang; Zhangjie Huang; Jiajia Li; Jinkai Qiu; Ying Zheng; Cheng Lian; Dongyun Chen; Long Chen; Qingfeng Xu; Jianmei Lu (Journal of Hazardous Materials, 2026)

The 9.2 ka event during the early Holocene recorded by a stalagmite from Dongge Cave - Chuntong He; Bin Zhao; Yongjin Wang; Kan Zhao; Shaohua Yang; Qingfeng Shao; Hai Cheng; Yijia Liang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Unveiling land competition through interaction networks: A consistency-based mining and simulation model that integrates inhibiting effects of land uses - Xun Liang; Jun-Long Huang; Qingfeng Guan (Landscape and Urban Planning, 2025)

Chinese speleothem evidence of the early-mid Holocene transition and the instability of Asian summer monsoon - Bin Zhao; Yongjin Wang; Kan Zhao; Jianjun Yin; Quan Wang; Shaohua Yang; Qingfeng Shao; Hai Cheng; Yijia Liang (Global and Planetary Change, 2025)

Centennial- to multidecadal-scale monsoon precipitation variability during the mid-Holocene - Yifei Wang; Zhenqiu Zhang; Yongjin Wang; Kan Zhao; Yijia Liang; Kui Gao; Jianshun Chen; Qingfeng Shao; Zeji Lu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Triple-synergistic dual-macrocyclic polysulfates for efficient capture of diverse iodine species - Jiajia Li; Jiaqing Huang; Xiaoyong Xia; Liang Liu; Chunyue Xu; Jinkai Qiu; Cheng Lian; Qingfeng Xu; Jianmei Lu (Journal of Environmental Chemical Engineering, 2025)

Monsoon and hydroclimate evolution during Heinrich Stadial 3 as revealed by stalagmite from Central China - Zhenjun Wang; Shitao Chen; Yongjin Wang; Li Wu; Shaohua Yang; Gongzhe Chen; Zhenqiu Zhang; Yijia Liang; Qingfeng Shao; Hai Cheng; R. Lawrence Edwards (Global and Planetary Change, 2025)

Ultrasound triggered spatial-temporal NO gas release to enhance sonodynamic therapy and immune checkpoint blockade therapy against pancreatic cancer - Wanrui Shi; Jianfeng Zhang; Ruiqi Wu; Shiti Shama; Shi Tan; Heng Xue; Yan Sun; Qingshuang Tang; Suhui Sun; Rui Tang; Guotao Feng; Xiaoda Li; et al. (Chemical Engineering Journal, 2025)

A triazine-tri-imidazole based cationic covalent organic polymer featuring high recyclability and radiation tolerance for efficient Re(Tc)O4- sequestration - Jiaqing Huang; Xiaoyong Xia; Jiajia Li; Liang Liu; Chunyue Xu; Jinkai Qiu; Cheng Lian; Qingfeng Xu; Jianmei Lu (Journal of Hazardous Materials, 2025)

Deciphering the regulatory network of carbon isotope discrimination in bread wheat through genome-wide association studies and genomic prediction - Qingfeng Dong; Shan Lu; Hao Ren; Dezheng Liu; Shen-ao Gao; Xuefen Cai; Shanshan Zhang; Muhammad Ateeq; Liang Chen; Yin-gang Hu (Theoretical and Applied Genetics, 2025)

Statistical investigation of marine bacterial extracellular polysaccharides: deciphering the interplay among environmental adaptation, species distribution, and biomedical potential - Yuanyuan Jiang; Shuo Liang; Qingfeng Niu; Chanjuan Liu; Guangli Yu; Guoyun Li (Marine Life Science & Technology, 2025)

Discovering directional relationships between urban morphology and thermal environment using an anisotropic 3D urban texture model - Zhewei Liang; Shengyu Jin; Huan Gao; Mengmeng Wang; Qingfeng Guan (Urban Climate, 2025)

Novel QTLs/genes affecting single stem elasticity, stem strength, and three lodging indices in bread wheat (Triticum aestivum L.) identified by genome-wide association analysis - Hao Ren; Shan Lu; Siting Li; Qingfeng Dong; Dezheng Liu; Roi Ben-David; Liang Chen; Yin-Gang Hu (Theoretical and Applied Genetics, 2025)

Microbially mediated mechanisms underlie N2O mitigation by bio-organic fertilizer in greenhouse vegetable production system - Lijun Ren; Lili Dong; Guopeng Liang; Yanyu Han; Jiaqi Li; Qingfeng Fan; Dan Wei; Hongtao Zou; Yulong Zhang (Applied Soil Ecology, 2025)

A new type of triploid fish derived from female Carassius auratus red var. × male Gobiocypris rarus - Fanglei Liu; Ziyi Huang; Xuanyi Zhang; Bei Li; Lujiao Duan; Jianming Yu; Qizhi Liu; Siyang Huang; Hongwen Liu; Qiuli Liang; Qingfeng Liu; Shaojun Liu (Aquaculture, 2025)

The impact of sub-pixel scale urban function on urban heat island: Insights derived from its decomposition - Qingfeng Guan; Yajun Li; Wenjia Huang; Wei Cao; Zhewei Liang; Jie He; Xun Liang (Applied Geography, 2025)

Variations of Asian summer monsoon and regional hydroclimate between the MIS 7.1 and 6.5 - Xiumin Zhai; Jingwei Zhang; Yi Li; Yijia Liang; Kan Zhao; Qingfeng Shao; Yongjin Wang; Xinggong Kong (Global and Planetary Change, 2025)

Deciphering the regulatory network of lignocellulose biosynthesis in bread wheat through genome-wide association studies - Qingfeng Dong; Hao Ren; Xuefen Cai; Yujie Zhang; Shan Lu; Dezheng Liu; Muhammad Ateeq; Liang Chen; Yin-Gang Hu (Theoretical and Applied Genetics, 2025)

Balancing simulation performance and computational intensity of CA models for large-scale land-use change simulations - Zhewei Liang; Xun Liang; Xintong Jiang; Tingyu Li; Qingfeng Guan (Environmental Modelling & Software, 2025)

El Niño-Southern Oscillation signals imprinted in stalagmite δ18O from 2005 to 2017 - Jianshun Chen; Yijia Liang; Kan Zhao; Yongjin Wang; Zhenqiu Zhang; Fucai Duan; Jingwei Zhang; Qingfeng Shao; Junji Zhu; Shaohua Yang; Lian Tang; Yuqing Wang; et al. (Quaternary International, 2025)

Mining genomic regions associated with stomatal traits and their candidate genes in bread wheat through genome-wide association study (GWAS) - Dezheng Liu; Shan Lu; Renmei Tian; Xubin Zhang; Qingfeng Dong; Hao Ren; Liang Chen; Yin-Gang Hu (Theoretical and Applied Genetics, 2025)

Experimental investigation on the ventilated cavitating flow characteristics around an axisymmetric body with an unsteady ventilation - Liang Hao; Housheng Zhang; Qingfeng Yang; Taotao Liu; Biao Huang; Guoyu Wang (Ocean Engineering, 2024)

Causal inference of urban heat island effect and its spatial heterogeneity: A case study of Wuhan, China - Yingqiang Zhong; Shaochun Li; Xun Liang; Qingfeng Guan (Sustainable Cities and Society, 2024)

HashGAT-VCA: A vector cellular automata model with hash function and graph attention network for urban land-use change simulation - Qingfeng Guan; Jianfeng Li; Yaqian Zhai; Xun Liang; Yao Yao (Landscape and Urban Planning, 2024)

Distribution and transformation of potentially toxic elements in cracks under coal mining disturbance in farmland - Yin Lu; Xin Xiao; Yan Liang; Junchi Li; Chunying Guo; Lili Xu; Qingfeng Liu; Yu Xiao; Shiyuan Zhou (Environmental Geochemistry and Health, 2024)

Orbital- and millennial-scale hydroclimate changes in central China during the last glacial period - Quan Wang; Kan Zhao; Yongjin Wang; Jianshun Chen; Yijia Liang; Yingfang Cui; Qingfeng Shao; Xiumin Zhai; Zhenqiu Zhang; Xinggong Kong; Hai Cheng; R. Lawrence Edwards; et al. (Quaternary Science Reviews, 2024)

Modeling the Subpixel Land-Use Dynamics and Its Influence on Urban Heat Islands: Impacts of Factors and Scale, and Population Exposure Risk - Xun Liang; Song Guo; Chunyang Huang; Bingyu Wang; Yao Xiao; Jie He; Yang Li; Mengmeng Wang; Qingfeng Guan (Sustainable Cities and Society, 2024)

Evaluation and projection of circulation conditions tied to summertime compound drought and heatwave frequency over the Yangtze River Delta, China, for the carbon neutrality period based on CMIP6 GCMs - Jing Wang; Ping Liang; Fei Cheng; Yanju Liu; Chengyu Song; Wei Wu; Qingfeng Zheng; Tianyu Zhang; Ping Qu; Yujie Li; Yihui Ding (International Journal of Climatology, 2024)
Frequent occurrences of compound droughts and heatwaves (CDHWs) may have considerable adverse impacts on human health and socioeconomic development. To project future summertime CDHWs over the Yangtze River Delta (YRD) of China under carbon neutrality (CN) for policymakers, we used nine global climate models (GCMs) from the Coupled Model Intercomparison Project Phase 6 (CMIP6) and evaluated and projected circulation conditions tied to the summer YRD CDHW frequency in the boreal summer. The results show that a marked mid‐tropospheric regional‐scale anticyclonic anomaly centred over the East China Sea can be deemed the dominant system linking the more frequent occurrence of YRD CDHWs. Our selected nine CMIP6 GCMs better captured the observed climatological and anomalous spatial circulation patterns connected to the summer YRD CDHW frequency. Moreover, the nine models' multi‐model ensemble mean (9MME) was better than most of the individual models regarding the related climatological circulation simulations. The 9MME‐projected changes in circulation conditions tied to summer YRD CDHWs during the carbon neutrality period (2050–2060) under SSP119 favour the comparable occurrence of the YRD with that for the same period under the medium greenhouse gas (GHG) warming scenario (SSP245), but the intensities of the CDHWs are the least severe. However, the highest number of YRD CDHWs is driven by the high GHG warming scenario (SSP585), and these CDHWs feature the most severe intensity. Our research identified a new paradigm regarding the frequency and intensity of the summer YRD CDHW under SSP119, highlighting the potential role of the newly accessible CN‐oriented sustainable development pathway in alleviating compound extremes.

Middle to late Holocene hydroclimate variability revealed by multi-proxy stalagmite records from Jinfo Cave, central-west China - Xiumin Zhai; Jingwei Zhang; Xinmiao Chen; Jianshun Chen; Kui Gao; Yijia Liang; Qingfeng Shao; Yongjin Wang; Xinggong Kong; Kan Zhao (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

An electrical conduction model for calcium-bearing shaly sandstone based on the effective medium Hanai-Bruggeman theory - Pengji Zhang; Yu Liang; Buzhou Huang; Fuyan Gou; Yangming An; Qingfeng Li; Hongzheng Li; Ruiyi Han (Acta Geophysica, 2024)

Evidence for the smallest fossil Pongo in southern China - Hua Liang; Terry Harrison; Qingfeng Shao; Jean-Jacques Bahain; Jinyou Mo; Yuexing Feng; Wei Liao; Wei Wang (Journal of Human Evolution, 2024)

Applicability and sensitivity analysis of vector cellular automata model for land cover change - Yao Yao; Ying Jiang; Zhenhui Sun; Linlong Li; Dongsheng Chen; Kailu Xiong; Anning Dong; Tao Cheng; Haoyan Zhang; Xun Liang; Qingfeng Guan (Computers, Environment and Urban Systems, 2024)

Distribution and transformation of potentially toxic elements in crack under coal mining disturbance - Junchi Li; Qinxue Yu; Ruoxi Qian; Xin Xiao; Yan Liang; Ping Luo; Hui Wang; Yin Lu; Lili Xu; Qingfeng Liu; Yu Xiao (Environmental Monitoring and Assessment, 2023)

Millennial-scale changes in the Asian monsoon during the MIS12 period as recorded by a Chinese stalagmite - Shaohua Yang; Shitao Chen; Yongjin Wang; Qingfeng Shao; Liangcheng Tan; Zhenqiu Zhang; Kan Zhao; Zhenjun Wang; Yijia Liang; Xiumin Zhai; Chuan-Chou Shen; R. Lawrence Edwards (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Specific pupylation as IDEntity reporter (SPIDER) for the identification of protein-biomolecule interactions - He-Wei Jiang; Hong Chen; Yun-Xiao Zheng; Xue-Ning Wang; Qingfeng Meng; Jin Xie; Jiong Zhang; ChangSheng Zhang; Zhao-Wei Xu; Zi-Qing Chen; Lei Wang; Wei-Sha Kong; et al. (Science China Life Sciences, 2023)

Study on time effect of acidified pulverized coal micro components and discussion on mathematical correlation of influencing factors - Qingfeng Xu; Shoujian Peng; Jiang Xu; Feng Jiao; Liang Cheng; Li Jia; Hailin Yang; Yan Yang; Rulin Liu; Seeram Ramakrishna (Fuel, 2023)

Middle Pleistocene Pongo from Ganxian Cave in southern China with implications for understanding dental size evolution in orangutans - Hua Liang; Terry Harrison; Qingfeng Shao; Jean-Jacques Bahain; Jianxin Zhao; Christopher J. Bae; Wei Liao; Wei Wang (Journal of Human Evolution, 2023)

Preparation of N-doped cellulose-based hydrothermal carbon using a two-step hydrothermal induction assembly method for the efficient removal of Cr(VI) from wastewater - Xinkun Zhao; Hongxu Liang; Zihao Wang; Daijia Li; Xiaoyan Shen; Xiaoya Xu; Kun Li; Qingyue Xiang; Yihan Wu; Qingfeng Chen (Environmental Research, 2023)

Ice-volume and insolation influences on hydroclimate changes in central eastern China during the antepenultimate glacial period - Quan Wang; Shayue Yuan; Yijia Liang; Kan Zhao; Qingfeng Shao; Zhenqiu Zhang; Junji Zhu; Xinggong Kong; Yongjin Wang; Jianghu Lan; Hai Cheng; Chengwei Xia; et al. (Science China Earth Sciences, 2023)

Development of suspension culture technology and hormone effects on anthocyanin biosynthesis for red Cyclocarya paliurus cells - Yuan Liu; Qi Liang; Daobang Tang; Yuqin Chen; Jianwei Zang; Wenjia Zhao; Jiguang Chen; Qingfeng Zhang; Zhongping Yin (Plant Cell, Tissue and Organ Culture (PCTOC), 2022)

Mechanism study of trans-lamina cribrosa pressure difference correlated to optic neuropathy in individuals with glaucoma - Qingfeng Liang; Leying Wang; Xuyang Liu (Science China Life Sciences, 2020)

Targeted disruption of tyrosinase causes melanin reduction in Carassius auratus cuvieri and its hybrid progeny - Qingfeng Liu; Yanhua Qi; Qiuli Liang; Jia Song; Junmei Liu; Wuhui Li; Yuqin Shu; Min Tao; Chun Zhang; Qinbo Qin; Jing Wang; Shaojun Liu (Science China Life Sciences, 2019)

The chimeric genes in the hybrid lineage of Carassius auratus cuvieri (♀)×Carassius auratus red var. (♂) - Qingfeng Liu; Yanhua Qi; Qiuli Liang; Xiujuan Xu; Fangzhou Hu; Jing Wang; Jun Xiao; Shi Wang; Wuhui Li; Min Tao; Qinbo Qin; Rurong Zhao; et al. (Science China Life Sciences, 2018)

Erratum to: Molecular characteristics of the ompA gene of serotype B Chlamydia trachomatis in Qinghai Tibetan primary school students - Xue Li; Shaoya Zhang; Qingfeng Liang; Mei Wang; Ailian Hu; Xiuyuan Li; Benshan Yang; Mingxin Zhang; Ningli Wang; Xinxin Lu (Science China Life Sciences, 2016)

Characteristics of pathogenic microorganisms found in 99 cases of conjunctivitis from the Qinghai Tibetan area - Benshan Yang; Xiuyuan Li; Qingfeng Liang; Shaoya Zhang; Shijing Deng (Science China Life Sciences, 2016)

Study of infectious conjunctivitis among children in rural areas of Qinghai province - Qingfeng Liang; Xinxin Lu; Mei Wang; Lei Tian; Antoine Labbé; Ailian Hu (Science China Life Sciences, 2016)

Molecular characteristics of the ompA gene of serotype B Chlamydia trachomatis in Qinghai Tibetan primary school students - Xue Li; Shaoya Zhang; Qingfeng Liang; Mei Wang; Ailian Hu; Xiuyuan Li; Benshan Yang; Mingxin Zhang; Ningli Wang; Xinxin Lu (Science China Life Sciences, 2016)

Enhancement of tocopherols in sweet corn by marker-assisted backcrossing of ZmVTE4 - Faqiang Feng; Qingfeng Wang; Chen Liang; Ruichun Yang; Xiaoqin Li (Euphytica, 2015)

Closing the yield gap could reduce projected greenhouse gas emissions: a case study of maize production in C hina - Zhenling Cui; Shanchao Yue; Guiliang Wang; Qingfeng Meng; Liang Wu; Zhiping Yang; Qiang Zhang; Shiqing Li; Fusuo Zhang; Xinping Chen (Global Change Biology, 2013)
Although the goal of doubling food demand while simultaneously reducing agricultural environmental damage has become widely accepted, the dominant agricultural paradigm still considers high yields and reduced greenhouse gas ( GHG ) intensity to be in conflict with one another. Here, we achieved an increase in maize yield of 70% in on‐farm experiments by closing the yield gap and evaluated the trade‐off between grain yield, nitrogen (N) fertilizer use, and GHG emissions. Based on two groups of N application experiments in six locations for 16 on‐farm site‐years, an integrated soil‐crop system ( HY ) approach achieved 93% of the yield potential and averaged 14.8 Mg ha −1 maize grain yield at 15.5% moisture. This is 70% higher than current crop ( CC ) management. More importantly, the optimal N rate for the HY system was 250 kg N ha −1 , which is only 38% more N fertilizer input than that applied in the CC system. Both the N 2 O emission intensity and GHG intensity increased exponentially as the N application rate increased, and the response curve for the CC system was always higher than that for the HY system. Although the N application rate increased by 38%, N 2 O emission intensity and the GHG intensity of the HY system were reduced by 12% and 19%, respectively. These on‐farm observations indicate that closing the yield gap alongside efficient N management should therefore be prominent among a portfolio of strategies to meet food demand while reducing GHG intensity at the same time.

A comparison of different optimization algorithms for retrieving aerosol optical depths from satellite data: an example of using a dual-angle algorithm - Xihan Mu; Qingfeng Shen; Zhao-Liang Li; Guangjian Yan; José Antonio Sobrino (International Journal of Remote Sensing, 2011)